Circulating Notch1 in response to altered vascular wall shear stress in adults. Issue 12 (2nd October 2022) - Badour, Matthew I.; Stone, Rachel M.; Parikh, Khushali S.; Lester, Nicholas J.; Meloche, Olivia L.; Wulterkens, Renee N.; Bain, Anthony R.
Abstract : New Findings: What is the central question of this study? Is the plasma concentration of Notch1 extracellular domain altered in response to decreased and increased vascular wall shear stress in the forearm in humans? What is the main finding and its importance? Notch1 extracellular domain is increased with acute increases in antegrade shear rate but does not change with 20 min of decreased shear rate caused by distal forearm occlusion. A novel and integral endothelial mechanosensor in humans that can help explain vascular endothelial adjustments in response to increases in antegrade shear stress was characterized. Abstract: Notch1 has been proposed as a novel endothelial mechanosensor that is central for signalling adjustments in response to changes in vascular wall shear stress. However, there remains no controlled in vivo study in humans. Accordingly, we sought to address the question of whether plasma concentrations of Notch1 extracellular domain (ECD) is altered in response to transient changes in vascular wall shear stress. In 10 young healthy adults (6M/4F), alterations in shear stress were induced by supra‐systolic cuff inflation around the wrist. The opposite arm was treated as a time control with no wrist cuff inflation. Plasma was collected from an antecubital vein of both arms at baseline, 20 min of wrist cuff inflation (low shear), as well as 1–2 min (high shear) and 15 min following (recovery) wrist cuff release. The Notch1 ECD was quantified using a commercially available ELISA. Duplex ultrasound was used to confirm alterations in shear stress. In the experimental arm, concentrations of Notch1 ECD remained statistically similar to baseline at all time points except for immediately following cuff release where it was elevated by ∼50% ( P = 0.033), coinciding with the condition of high antegrade shear rate. Concentrations of Notch1 ECD remained unchanged in the control arm through all time points. These data indicate that Notch1 is a viable biomarker for quantifying mechanotransduction in response to increased shear stress in humans, and it may underlie the vascular adaptations or mal‐adaptations associated with conditions that impact antegrade shear.